Implementation of Cyber-Security Enterprise Architecture Food Industry in Society 5.0 Era - Sari, Ratih Titi Komala; Hindarto, Djarot (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The application of Enterprise Architecture is an important topic in the development of the food industry in the Society 5.0 Era. Enterprise Architecture is used to integrate and optimize corporate information systems so as to generate higher business value. This study aims to evaluate the effectiveness of Enterprise Architecture implementation in improving the performance of the food industry in Era Society 5.0 and implementing Cyber-Security as a defense against the system to be implemented. This study uses a case study method by collecting data from several companies in the food industry. The data collected includes information about the implementation of Enterprise Architecture, business performance, and factors that influence the successful implementation of Enterprise Architecture. The results of the study show that the implementation of Enterprise Architecture has helped companies improve their business performance, especially in terms of operational efficiency, better decision making, and the ability to adapt to changes in the business environment. Factors that influence the successful implementation of Enterprise Architecture include management support, involvement of business users, and availability of resources. In conclusion, the application of Enterprise Architecture can help the food industry in Era Society 5.0 improve its business performance. However, the implementation of Enterprise Architecture must be accompanied by strong management support, greater involvement of business users, availability of adequate resources and adequate Cyber-Security. The novelty of this research is implementing Cyber-Security as protection in implementing Enterprise Architecture.